Fundamental behavior for biosorption of divalence cations by pleurotus mushroom spent-substrate - Tay, C.C.; Redzwan, Ghufran; Hooi, L.H.; Kong, Y.S.; Surif, S.; Abdul-Talib, S. (Faculty of Science, University of Malaya, 2012)

(untitled)
Biosorption behavior of Pleurotus mushroom spent-substrate was studied using two divalence cations: Ni(II) and Cu(II). Biosorption of both cations showed similar behavior on the effect of pH, initial concentration, temperature and contact time. Optimum biosorption was found to be between pH of 5-6, while lower initial concentration and temperature (as low as 10 mg.L-1 and 5 °C), increased the biosorption efficiency. Rapid biosorption was observed to occur within 4-5 minutes of contact time. Therefore, metal removal using PMSS as the biosorbent needs to address the four fundamental parameters.